Performance Analysis to Improve Quality of Service Using Cluster Based Hidden Node Detection Algorithm in Wireless Sensor Networks. Issue 2 (2nd April 2016) - Rohini, R.; Gnanamurthy, R.K.
Abstract: This paper investigates the Hidden Node (HN) problem in wireless sensor networks. Hidden node occurs in the networks when nodes outside the carrier-sensing range of each other are nevertheless close enough to interfere with each other. As a result, the carrier sensing mechanism may fail to prevent packet collisions. Hidden node can cause many performance problems, including throughput and energy degradation and increases in delay. In this paper, a novel clustering mechanism based on energy consumption is proposed to detect the hidden nodes in the wireless sensor networks to improve the network performance. The performance of the network is analyzed using the parameters — energy consumption, delay and throughput, with or without hidden nodes in the network.